Exploring Factors That Influence Computational Thinking Skills in Elementary Students' Collaborative Robotics. (October 2021) - Stewart, William H.; Baek, Youngkyun; Kwid, Gina; Taylor, Kellie
Recently educational robotics has expanded into curriculum beyond traditional STEM fields, and which can also be used to foster computational thinking (CT) skills. Prior research has shown numerous interdisciplinary benefits related to CT, however, these influential factors have often been investigated with relatively few variables. This study investigated factors that may lead to 4th and 5th grade elementary school students' development of computational thinking skills in collaborative robotics activities by hypothesizing a model which proposed that a problem solving inventory, intrinsic motivation, and enjoyment were the main predictors of computational thinking skills. The model was then tested by surveying students with several psychometric inventories where a revised model was then constructed. The study found significant relationships between perceived competence and enjoyment, and learning motivation, and intrinsic motivation. Another important finding was that problem solving was a significant predictor of computational thinking skills. Results were interpreted with reference to implications for possible means of improving learning outcomes when using collaborative robotics in an educational setting.